A Homoeopathic Approach to Managing Menstrual Health-A Review Article - Bhatt, Priyanka; Bhardwaj, D.K.; Dwivedi, Shreya; Bishwas, Rinku; Biswas, Ruchi (Journal of Neonatal Surgery, 2025)
PRE-MENSTRUAL SYNDROME (PMS) is a group of symptoms, which are physical, mental and behavioral, arising days before the onset of menstrual period. Usually, the symptoms disappear after the menstrual flow begins. This period of PMS is observed during luteal phase of menstrual cycle. The symptoms are characterized by irritability, anxiety, emotional lability, depression, oedema, bloating, breast pain, acne, fatigue and headache occurring during the 7 to 10 days before and usually ending a few hours after the onset of menses. This article aims to explore the potential of Homoeopathy in the management of PMS, focusing on the remedies commonly used in clinical practice, the principles behind their selection, and the evidence supporting their efficacy.